Implementasi Model Pembelajaran Sentra Cooking Class dalam Mengembangkan Sikap Kemandirian Anak Usia Dini di RA Zu Tsaqif - Qisthina Hsb; Sri Wahyuni; Fakih Hakim Hasibuan (Institut Nalanda, 2024)
This research aims to identify the independence of the child through the learning model of the cooking class center at RA Zu Tsaqif. Learning center is a strategy in learning that is implemented in the circle (circle time). Sentra cooking class is a cooking activity processing raw materials ready-to-eat food using materials or tools by children safely. In obtaining data on research the author applies qualitative research through data obtained from observations, interviews and documentation. The use of data analysis techniques is data reduction, data presentation and conclusion drawing. This study is the subject of 15 children. The results of the study showed that: 1) The independence of children in RA Zu Tsaqif majority develops very well (BSB) 8 people, develops according to expectation (BSH) 4 people, and children who begin to develop (MB) 3 people. 2) Implementation of the learning model of the cooking class center in RA Zur Tsaquif is divided into three stages namely the first stage (opener), the core stage and the final stage (penutup). 3) The effort given is guidance and instruction to the child and to play.